American heroes - Patterson, James, 1947-; Eversmann, Matt; Malloy, Tim (Journalist); Mooney, Chris (Little, Brown and Company, 2024)
"U.S. soldiers who served in overseas conflicts--from World War II, Korea, and Vietnam to Iraq and Afghanistan--share true stories of the actions that earned them some of America's most distinguished military medals, up to and including the Medal of Honor. They never acted alone, but always in the spirit of camaraderie, patriotism, and for the good of our beloved country. There has never been a better time for all of us to think about duty, sacrifice, and what it means to be an American hero"--